Kajian Semiotika Elemen Arsitektural Mushola Babah Alun Di Taman Suropati Kota Jakarta - Thomas, Enrico; Jariyah, Vina Ainun; Ibadi, Raden Mohamad Wisnu (Jurnal Lingkungan Karya Arsitektur, 2024)
Babah Alun Mushola at Taman Suropati Menteng Jakarta is one of the 7 Islamic prayer places which initiated by Jusuf Hamka. Babah Alun Mushola placed on the upper floor police station building at Taman Suropati Menteng Jakarta . According to Jusuf Hamka, the architecture of this Building was designed with application of Betawi, Chinese and Dutch Colonial cultural architectural elements. This research aims to determine the application of those signs through Pierce’s semiotic theory to identify the architectural elements of the Babah Alun Taman Suropati mushola. This research was carried out using a descriptive qualitative approach, by observing the details of the cultural architectural elements at the Babah Alun Taman Suropati mushola. The research exploring the form, function and symbolic meaning of the application of the cultural architecture elements. It is hoped that the research results can become a reference in designing building designs that apply cultural architectural elements